Respuesta :
Answer:
[tex]7x^2 - 40x + 12 = 0[/tex]
Step-by-step explanation:
The equation [tex]\frac{5x-2}{2}-\frac{19x-6}{2x}=\frac{3x-2}{4}[/tex] can be written as a quadratic with the following steps:
- Multiply each term by 4x to clear all denominators.
- Apply the distributive property.
- Combine like terms.
- Move all terms to one side.
Step 1 :
[tex]\frac{5x-2}{2}-\frac{19x-6}{2x}=\frac{3x-2}{4}\\4x(\frac{5x-2}{2}-\frac{19x-6}{2x}=\frac{3x-2}{4})\\2x(5x-2) -2(19x-6) = x(3x-2)[/tex]
Step 2:
[tex]2x(5x-2) -2(19x-6) = x(3x-2)\\10x^2 - 4x - 38x + 12 = 3x^2 - 2x[/tex]
Step 3:
[tex]10x^2 - 4x - 38x + 12 = 3x^2 - 2x\\10x^2 - 42x + 12 = 3x^2 - 2x[/tex]
Step 4:
[tex]10x^2 - 42x + 12 = 3x^2 - 2x\\7x^2 - 40x + 12 = 0[/tex]
Answer:
7x-40x-12=0
Step-by-step explanation:
I know because I got it wrong following on of the other mentally disabled individuals who posted an innacurate answer here. Your welcome for an accurate answer from a semi intelligent individual. : )